Model Predictive Speed Control of a Wind Turbine System Test Bench. Issue 32 (2018) - Leisten, Christian; Jassmann, Uwe; Balshüsemann, Johannes; Abel, Dirk
Abstract: This paper presents a Model Predictive Speed Control of a Wind Turbine System Test Bench. A System Test Bench enables the investigation of the total Wind Turbine drive train dynamic by replacing the rotor and the grid with a controllable load application system. Its basic and safe operation mode is speed control. This must be robust and offer both a dynamic reference tracking and disturbance rejection of the generator torque of the testee while considering the actuator limitation of the motor. Aside, due to the missing rotor, the frequency response of the Wind Turbine drive train on the System Test Bench strongly differs from the original one. The resulting shifted eigenfrequencies must be actively damped for a safe and realistic operation. The Model Predictive Control presented in this paper naturally satisfies all these requirements. The developed control is validated in simulation showing excellent results. Also, it is implemented on a real time system at the System Test Bench and put into first operation at full load of the Wind Turbine. The generator speed is already controlled stably at the rated power PrWT = 2.75MW oppressing generator torque steps. However, it shows an oscillation around the operating point, so further work must be done to reproduce the same control quality in experiment.